The ecology of coexistence and conflict in Cyprus : exploring the religion, nature, and culture of a Mediterranean island - Dietzel, Irene, 1979- (Religion and society (Hague, Netherlands), 2014)
What is the significance of sustainable resource management for the functioning of Mediterranean island societies? How do human-environment relations reflect in a multi-ethnic religious landscape? This book poses these questions in the context of the Ottoman, British, and modern history of Cyprus. It explores the socio-ecological dimension of the Cyprus Conflict and considers the role of local environmental practices for historical coexistence and modern division. The book synthesizes theoretical approaches from the research on 'religion and ecology' with the anthropology of Cyprus, with the goal to develop and establish an ecological perspective on coexistence and conflict in the Mediterranean.